Kochen-Specker Theorem for a Single Qubit - Toh, Sing Poh; Zainuddin, Hishamuddin (Institute for Mathematical Research, 2008)
The Kochen-Specker theorem (KS) states that Ilonconrextual hidden variable theories are incompatible with quantum mechanics. Since the first proof of the theorem, von Neumann projection measurement has been used and the quantum system considered has dimensionality of at least three. However, recently generalized measurements represented by positive-operator-va!ued measures (POVM) have been applied to extend the proof to two dimensional quantum systems. This note gives numerical calculations on the first KS proof for a single qubit.